Lightweight hybrid materials and structures for energy absorption: A state-of-the-art review and outlook - Sun, Guangyong; Chen, Dongdong; Zhu, Guohua; Li, Qing (Thin-walled structures, 2022)
Lightweight materials and structures have attracted tremendous interests for their compelling advantages in a range of engineering problems that have placed heightened requirements in safety, environment, competitiveness and cost over recent years. As an effective approach, hybrid systems aim to take advantages and characteristics of different materials to maximize their functional roles in lightweight structures, thereby enhancing their respective material efficiency. This article provides a critical review on the advances in hybrid materials and structures for crashworthiness and energy absorption performance, in which fiber reinforced plastic (FRP), metals, cellular fillers and their hybrid configuration are discussed respectively. Attention is paid to the hybridization of different forms of FRP-FRP, FRP-metal, cellular filling materials with FRP structures, thereby demonstrating their constructive characteristics for different design goals. Crashworthiness and energy absorption performances of various hybridized materials, such as carbon fiber reinforced plastic (CFRP), glass fiber reinforced plastic (GFRP), aluminum/steel, metallic foams/honeycombs/lattices, are evaluated and compared in detail. After highlighting the knowledge gaps in existing literatures, this review provides an outlook on the possible future research. It is expected to gain new insights into the design of novel lightweight hybrid configurations for aerospace, automotive, nautical and railway applications. •Constituent materials and preparation technology of hybrid energy absorption structures.•Experimental characterization and modeling of hybrid energy absorption structures.•Failure mechanism and parameter analysis of hybrid energy absorption structures.•Current challenges and future developments of hybrid energy absorption structures.